Prolonged-heated High-Fat Diet Increase the Serum LDL Cholesterol Level and Induce the Early Atherosclerotic Plaque Development in Wistar Rats - Yurina, Valentina; Yunita, Ema Pristi; Raras, Tri Yudani Mardining; Rudijanto, Achmad; Handono, Kusworini (Journal of Tropical Life Science, 2019)
Rats are one of the most widely used animal models in health research. However, since rats are relatively resistant to atherosclerosis, the transgenic rats often used to study atherosclerosis in rats. Our study suggests a prolonged-heated lipid to induce atherosclerosis in rats, therefore provide a more low-cost option to study atherosclerosis in rats. Aims of this study is to compare the effect of heated high-fat diet (HFD) to the LDL and HDL cholesterol level and foam cell formation in the Wistar rat animal model. Rats were divided into three groups, control group was given with the normal diet, and the other two treated groups received oxidized HFD (heated HFD) and HFD, respectively. The heated HFD contain lard that was previously heated at 190Â°C for 24 h. Diet was given for 8 weeks. The serum LDL and HDL cholesterol level were measured before and 4th and 8th weeks after treatment with help of colorimetric measurement. The aorta analyzed for the foam cell formation after HE staining using the light microscope.Â  The prolonged- heated HFD significantly increased the LDL cholesterol from the 4th week of the treatment (p = 0.023). The rats aortic from HFD and heated HFD treated groups showed a mononuclear cells infiltration and the early foam cell formation. The heating process of the lipid caused lipid oxidation which significantly increased the LDL cholesterol level of the animal model and foam cells formation. This study suggests that Wistar rats with heated HFD could demonstrated early atherosclerosis plaque development.